UPAYA MENINGKATKAN AKHLAKUL KARIMAH SANTRI MADRASAH DINIYAH NURUL HUDA KECAMATAN PRAMBON KABUPATEN SIDOARJO - Miftakus Surur, Agus; Anggraini, Atika; Nafi’ah, Nabilatun (Proceedings of Annual Conference on Community Engagement, 2023)
Madrasah Diniyah Nurul Huda is a non-formal educational institution located in Kajar Tengguli Village, Prambon subdistrict, Sidoarjo district. One of the aims of research at the Nurul Huda Islamic Madrasah is to implement the tri dharma of higher education on the pillar of community service, one of which is by improving the morals and morals of Nurul Huda Islamic Madrasah students. Because morals in a child really need special attention from both parents and teachers as educators, apart from that, morals are also a very important part to instill and improve in a child. Children who have good morals will later make the child have a personality that is of course also good. There are several ways or efforts made to improve the morals and morals of Nurul Huda Madrasah Diniyah students, namely by being directly involved in learning activities, holding recitation activities based on the Ta’lim Muta’allim book and implementing a culture of greeting, greeting, smiling, being polite and courteous when Nurul Huda Madrasah Diniyah students passed each other. Deliberation on moral matters. The aim of this research is to improve the morals and morals of Nurul Huda Madrasah Diniyah students. This research uses the ABCD method, which is a technique for finding people’s abilities to be able to manage the assets, strengths and potential they have. So it is seen as capable of moving and motivating them to make changes as well as being the main actors of change (Pilot Project). The results of the activity showed that there was an increase in the morals and morals of Nurul Huda Madrasah Diniyah students. The students and teachers of Madrasah Diniyah Nurul Huda are very grateful for the benefits gained from implementing the program as an effort to improve the morals of Madrasah Diniyah Nurul Huda students.